A role for IL-1B in oxidative stress-mediated neuronal impairment - O'Donnell, Eamonn (Trinity College (Dublin, Ireland). Department of Physiology, 2000)
The aims of this study were to; (1) investigate age-related changes in the antioxidant defence system in the rat cortex and hippocampus; (2) investigate the role of IL-1β in influencing oxidative stress in brain tissue of aged and stressed rats; (3) to establish the efficacy of dietary supplementation with antioxidants in reversing the functional impairment seen in the hippocampus of stressed and IL-1β-treated rats.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin